Beliefs influencing students' career choices in Sweden and reasons for not choosing the accounting profession. (March 2022) - Karlsson, Per; Noela, Massa
Highlights: Behavioral, normative beliefs influence student intention to not choose accounting. Behavioral beliefs include no interest in accounting and believing it to be boring. High salaries in other professions influence the intention not to choose accounting. Normative beliefs are formed under the influence of teachers and peers. Working accountants could help mitigate the accountant deficit in Sweden. Abstract: This study, employing the simplified Theory of Reasoned Action (TRA), investigates student beliefs that influence their attitudes and subjective norms, leading them to not choose the accounting profession in Sweden. Questionnaires were sent electronically to first-year and second-year university students, and, after applying the exclusion criteria, the sample size comprised 228 students. The results reaffirmed the simplified TRA model and revealed that both behavioral (no personal interest in accounting, a boring profession, and higher salaries in other occupations) and normative beliefs (the influence of teachers and peers), through personal attitudes and subjective norms, influenced students' decision to avoid the accounting profession. The findings suggest that accounting departments and business school faculties should recruit professional accountants and invite Swedish professional accounting bodies to create supportive activities that will motivate and help students learn more about the profession. Furthermore, accounting teachers should be more practical and equipped with engaging pedagogical techniques, and mandatory internships and seminars should be included in the school curriculum. It is also suggested that these implications should be positively communicated through social media.